2011
DOI: 10.3844/jssp.2011.257.264
|View full text |Cite
|
Sign up to set email alerts
|

The Perceived Leader Support Behavior for Subordinate's Creativity: The Moderating Effect of Trust

Abstract: Problem statement:The main goal behind this study tries to figure out whether or not the leader's supportive behavior will influence subordinates' creativity and is there any affection of trust between leaders' supportive behavior and subordinates' creativity? Approach: This study was conducted to examine the relationships between leader support behavior and subordinate creativity and the moderating effect of trust on subordinates' creativity under the leader support behavior. Results: From the analysis, we fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 41 publications
(38 reference statements)
1
7
0
Order By: Relevance
“…The results of current study confirm our assumption that social exchange relations foster creativity (creative involvement in this study), these results are consistent with previous studies on exchange relation and creativity association e.g. Atwater and Carmeli (2009);Cattani and Ferriani (2008); Carmeli and Schaubroeck (2007); Chen et al (2011);Mumford et al (2002); Oldham and Cummings (1996); Stokols et al (2002); Wang et al (2010). All these studies have witnessed the significant role of social exchange relations and creativity, but none of them focused on social support (supervisor & coworker support) in predicting creative involvement.…”
Section: Discussionsupporting
confidence: 93%
“…The results of current study confirm our assumption that social exchange relations foster creativity (creative involvement in this study), these results are consistent with previous studies on exchange relation and creativity association e.g. Atwater and Carmeli (2009);Cattani and Ferriani (2008); Carmeli and Schaubroeck (2007); Chen et al (2011);Mumford et al (2002); Oldham and Cummings (1996); Stokols et al (2002); Wang et al (2010). All these studies have witnessed the significant role of social exchange relations and creativity, but none of them focused on social support (supervisor & coworker support) in predicting creative involvement.…”
Section: Discussionsupporting
confidence: 93%
“…Another widely cited definition of "culture" is from Hofstede (2001), who refers to organizational culture as the 'collective programming of the mind' that differentiates one organization from another. An organizational culture can be observed through norms, actions and rules and develops through communication and relationships among organizational members (Chen et al, 2011). This interaction helps members understand how the organization operates, which subsequently influences the members' judgments and behaviors (Lillis and Tian, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Studies also found that the employees who lacked sufficient support from their leaders did not show better performance (Imtiaz and Ahmed, 2009). It is also found that the higher degree of trust from leaders to employee will cause the higher performance on employees' creativity thinking and action (Chen et al, 2011).…”
Section: Leader's Support and Organisational Performancementioning
confidence: 98%